The study of outdoor air particulate matter concentration and composition at the front gate and rear gate of UITM Shah Alam, Malaysia / Mohd Fairul Mohd Saad - Mohd Saad, Mohd Fairul (Faculty of Applied Sciences, 2009)
study was conducted at the front gate and rear gate of Universiti Teknologi Mara (UiTM) for outdoor air quality. The indicators of air pollutant monitored were lead (Pb), copper (Cu), zinc (Zn), and calcium (Ca) in particulate matter (PM10). The instrument used for this study was the Air Mini-Volume sampler and Inductively Couple Plasma with Optical Emission Spectrometer (ICP-OES). The monitoring was conducted during the semester on weekdays and on weekend. Result from this study show level of air pollutants (PM10) at the front gate and rear gate was generally high. The highest value of total particulate matter (PM10) measurement can reach almost 343.46µg/m³, exceeding Malaysian Ambient Quality Guidance of 150µg/m3.